2010
DOI: 10.4314/acsj.v17i1.54209
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall and temperature effects on flowering and pollen productions in cocoa

Abstract: Production of non-functional pollen by plant reduces effectiveness of pollination. A study was carried out at Cocoa Research Institute of Nigeria, Ibadan to determine the influence of rainfall and temperature on flowering intensity of selected clones of Upper Amazon cocoa (Theobroma cacao), as well as its pollen fertility. Eight clones of T. cacao used were T17/11, T7/12, T12/5, T86/45, C23, C64, C77 and Pa 24. The number of flowers at varying locations was recorded. The anthers were squashed in acetocarmine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 5 publications
6
19
0
16
Order By: Relevance
“…The tree-to-tree differences in the production of floral buds, opening of flowers, and formation of cherelles are consistent with the findings that cocoa flower initiation, shape and morphogenesis though dependent on the environment is regulated endogenously [22,23]. The monthly mean variations in the floral and fruit productions as well as fruit losses appeared to be the same during certain times of the year from September to December.…”
Section: Flowering Patternssupporting
confidence: 73%
See 1 more Smart Citation
“…The tree-to-tree differences in the production of floral buds, opening of flowers, and formation of cherelles are consistent with the findings that cocoa flower initiation, shape and morphogenesis though dependent on the environment is regulated endogenously [22,23]. The monthly mean variations in the floral and fruit productions as well as fruit losses appeared to be the same during certain times of the year from September to December.…”
Section: Flowering Patternssupporting
confidence: 73%
“…Low light intensities suppress flower production in cocoa [29], and high light intensity though detrimental to the photosynthetic apparatus of cocoa is reported to stimulate flowering [30,31]. Omolaja et al [23] observed that high temperature and increased rainfall promote flushing and flower initiation and flowering intensity in cocoa. The fact that the cocoa flowered from the beginning of the raining season probably meant that cocoa reacts to the stimulus of water.…”
Section: Effect Of Climatic Conditions On Flower Productionmentioning
confidence: 99%
“…Akibatnya, pertumbuhan dan produksi kakao menurun (Araque et al, 2012). Selain terhadap perkembangan biji (Osei-Bonsu, Ameyaw, Amoah, & Oppong, 2002;Oyekale, Bolaji, & Olowa, 2009;Moser et al, 2010), ketersediaan air juga berpengaruh pada fase perbenihan (Razi, Halim, Kamariah, & Noh, 1992) dan periode pembentukan bunga (Wood, 1975 cited in Omolaja, Aikpokpodion, Oyedeji, & Vwioko, 2009). Lebih lanjut dilaporkan Mommer (1999) bahwa sekitar 80% dari buah muda (cherelle) tidak akan mencapai matang akibat layu (cherelle wilt).…”
Section: Pendahuluanunclassified
“…Unsur iklim yang paling berpengaruh terhadap pertumbuhan vegetatif, pembungaan, dan pembuahan kakao di antaranya ialah curah hujan dan suhu (Adjaloo et al, 2010;Ojo dan Sadiq, 2010;Omolaja et al, 2009 ). Oleh karena itu, kakao yang ditanam di bawah kondisi agroekosistem iklim kering akan memiliki karakteristik pertumbuhan dan hasil yang berbeda dengan yang ditanam pada agroekosistem iklim basah.…”
Section: Pendahuluanunclassified